Orbita Taban Kırıkları ve Cerrahi Tedavisinde Kullanılan İmplantlar - Boz, Ali Altan Ertan (Göz Hastalıklarında Güncel Çalışmalar VI-Güz, 2024)
Orbita taban kırıkları en sık görülen orbita duvar kırığıdır. Tanısında maxillo-fasyal bilgisayarlı tomografi görüntülemesi altın standarttır. Cerrahi endikasyonlar ve müdahale zamanı hastanın başlangıçtaki klinik durumuna bağlıdır. Genellikle, ilk 7-10 gün ödem, kanama ve diplopinin geçmesi açısından hastalar gözlenmelidir. Persistan diplopi, enoftalmus, ekstraoküler hareket kısıtlılığı ve okülokardiyak refleks varlığı genellikle cerrahi onarım gerekliliğini belirleyen ana faktörlerdir. Cerrahi teknikte genellikle güvenli olan transkonjonktival yaklaşım tercih edilir. İdeal rekonstrüksiyon materyali konusunda literatürde hala bir konsensus bulunmamaktadır. İmplant seçiminde en iyi sonuç alınabilen ve en düşük komplikasyon oranına sahip implantlar seçilmelidir. İdeal materyal rezorbabl, osteokondüktif, enfeksiyona dirençli, minimum derecede reaksiyon gösteren, kemik büyümesine izin veren, ucuz ve kolayca bulunabilir olmalıdır. İmplantların bilgisayar destekli 3 boyutlu baskı tekniği ile üretilmesi orbital taban kırıkları onarımında kişiye ve kırığa özel implantların geliştirilmesine ve komplikasyonların azalmasına yardımcı olacaktır. Orbital floor fractures are the most common type of orbital wall fracture. Maxillofacial computed tomography imaging is considered the gold standard for diagnosis. Surgical indications and timing of intervention depend on the patient's initial clinical presentation. Typically, patients should be observed for the first 7–10 days to allow for the resolution of edema, hemorrhage, and diplopia. Persistent diplopia, enophthalmos, restricted extraocular movements, and the presence of an oculocardiac reflex are the primary factors that generally necessitate surgical repair. The transconjunctival approach, which is considered generally safe, is preferred in most surgical techniques. There remains no consensus in the literature regarding the ideal reconstruction material. The selection of implants should prioritize those that yield the best outcomes with the lowest complication rates. The ideal material should be resorbable, osteoconductive, resistant to infection, minimally reactive, promote bone growth, and be cost-effective and readily available. The use of computer-assisted 3D printing techniques in implant production can aid in the development of patient- and fracture-specific implants for orbital floor fracture repair, thereby reducing complications.